2022
DOI: 10.21203/rs.3.rs-2163737/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of Alstonia Angustiloba Tree Water Uptake on Slope Stability: A Case Study at the Unsaturated Slope, Pahang, Malaysia

Abstract: This study examines the effects of tree water uptake at different depths and distances on the improvement of induced water uptakes in soil owing to transpiration. This study is performed to examine the tree water uptake profile in a vegetated slope with the existence of Alstonia Angustiloba mature tree at the top and the permanence of the slope during various precipitation penetration events by which the data of the tree water uptake produced within this section of the slope is recorded and implemented to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…5. The unaltered kaolinitic clay had an MDD of 1.55 g/cm 3 and an OMC of 21%, which is identical to the findings reported by previous investigations [23][24]. The kaolinitic clay samples showed a reduction in MDD and OMC value when the soil was altered with 2% SF, with an MDD and OMC of 0.04 g/cm 3 and 3.0%.…”
Section: Mechanical Properties Of Kaolinitic Clay and Altered Kaolini...supporting
confidence: 87%
See 2 more Smart Citations
“…5. The unaltered kaolinitic clay had an MDD of 1.55 g/cm 3 and an OMC of 21%, which is identical to the findings reported by previous investigations [23][24]. The kaolinitic clay samples showed a reduction in MDD and OMC value when the soil was altered with 2% SF, with an MDD and OMC of 0.04 g/cm 3 and 3.0%.…”
Section: Mechanical Properties Of Kaolinitic Clay and Altered Kaolini...supporting
confidence: 87%
“…The kaolinitic clay samples showed a reduction in MDD and OMC value when the soil was altered with 2% SF, with an MDD and OMC of 0.04 g/cm 3 and 3.0%. MDD steadily increased to 1.51 g/cm 3 and 1.52 g/cm 3 when SF levels of 4% and 6% were used, while OMC continuously decreased to 17.5% and 17.9%, respectively. The increase in OMC was symmetrically limited, due to the lower specific gravity and heterogeneous particle size of the SF, resulting in the formation of enlarged cavities However, the findings were contradictory to the research by Türköz et al [22], which showed that the use of 2%, 4%, and 6% of SF reduced the specific gravity of kaolinitic clay but did not substantially affect its grain size, resulting in a slight reduction in OMC for the different utilization ratios of SF.…”
Section: Mechanical Properties Of Kaolinitic Clay and Altered Kaolini...mentioning
confidence: 94%
See 1 more Smart Citation
“…This continuous rise in PL with the addition of SF can be attributed to cation exchange between kaolinite clay minerals and positive cations present in SF. The decrease in plasticity properties of kaolinite clay was a consequence of substituting highly plastic clay particles with less reactive SF particles, leading to flocculation and a subsequent reduction in consistency limits, as discussed by Zaini et al [15] and Zaini et al [16]. The PL and LL value of the stabilized kaolinite clay were also reduced when different percentages of lime were utilized with 6% of SF.…”
Section: Atterberg Limitmentioning
confidence: 87%
“…Therefore, it has a high potential to replace conventional aggregates for various engineering purposes. Beneficial use of bottom ash as replacement material in stone column offer an attractive alternative of disposal due to the substantial economic savings which can be attained by the reduction of ash disposal costs and the conservation of natural soils and lands [17][18][19]. This study is therefore aimed in investigating the enhancement of strength of soft clays when it is reinforced with singular bottom ash column as a replacement for the stone column.…”
Section: Introductionmentioning
confidence: 99%